Strategi Pencegahan Kecurangan Akademik Mahasiswa Akuntansi Pada Program Magang Industri - Rezky Oktaviahidayanti Syamsul; Muhammad Ramadhan Slamet; Diah Amalia; Febrina Wulandari; Yunisha Anjali Rahma; Wiansri Syahmawuli (Politeknik Negeri Batam, 2023)
The aims of this study are 1) to identify the factors that are the root cause of the vulnerability of academic fraud committed by Perguruan Tinggi ABC accounting students on administrative internship documents in the form of soft files, and 2) determine strategies to prevent acts of academic fraud committed by Perguruan Tinggi ABC accounting students. on the internship administrative documents in the form of soft files. The type of research is descriptive research. The data collection method used in this research is the method brainstorming. The results of this study are 1) the factors causing academic fraud committed by Perguruan Tinggi ABC accounting students on internship administrative documents in the form of soft files, namely man, material, measurement, method, machine and mother nature; and 2) The strategy formulated to prevent acts of academic fraud committed by Perguruan Tinggi ABC accounting students on internship administrative documents in the form of soft files is to prepare staff specialfor internship administration, design applications for internships, monitor regularly between Internship Supervisors and Supervisors, make documents and technical guide videos, and helpdesk related to the internship program.